SRI LANKA: Climate & food security monitoring bulletin May-September 2020 - CGIAR Research Program on Water, Land and Ecosystems; International Water Management Institute (CGIAR Research Program on Water, Land and Ecosystems, 2020)
The harvest of paddy and other food crops in 2020 was above-average compared to the past few years. Major reservoir storage levels are at 39% of their capacity at present, which is well above average.